Suffering of the body and mind: Predictors for psychosomatic problems in feamle refugees - Ljubotina, Damir (Array, 1998)
In a sample of 120 female refugees, tests were carried out regarding the level of various health problems and a number of factors which according to the suggested model, influence the level of adjustment. Each subject was asked to state whether a given symptom had been present before the war. This provided us with information about the level of problem before the experienced traumatic events. The most frequent somatic and psychological symptoms are reported. Many of the somatic symptoms indicate a high level of physiological arousal indicative of PTSD reactions, anxiety, and depressive states. Correlation between health problems before and after the war is higher than 0.40, and implies the importance of previous health status, primarily for somatic problems. The general level of health problems is significantly increased in comparison to the period prior to the war. There is a high correlation between somatic and psychological symptoms. After trauma, body and mind suffer simultaneously. Important predictors found were the extent of experienced traumatic events, losses of relatives, age, and level of health prblems before the war.